PENINGKATAN PRESTASI BELAJAR FISIKA DENGAN PEMBELAJARAN PETA PIKIRAN (MIND MAPPING) PADA PESERTA DIDIK XII IPA 1 SMAN JATIROTO - Iin Eko Sundari (Pendidikan Biologi,Universitas Islam Jember, 2015)
This research is a classroom action research on Performance Improvement Learning Physics Learning Model Using Mind Mapping. This study was conducted in SMA Jatiroto. Subyek study were all students of class XII IPA 1 were 26 students consisting of 8 male students and 18 female students. Characteristics class research subjects are students in this class mostly tend to be quiet, still less open in issuing his opinion. The method used in this research is classroom action research (PTK). Each cycle includes: planning (plan), (2) action (action), (3) observation (observation) and (4) reflection (reflection).The activities of teachers has increased from the first cycle or worth 78.4 3.92 to 4.25 of the classification be Good Enough. Increased activity of students from the first cycle to the second cycle ie from 2.99 into 4.04. Study results of students also increased, namely the minimum value of 50 to 60 students, the maximum value of 90 to 100 and average value of 71.3 to 80.4. Completeness showed an increase that is from who completed a total of 14 to 22. Mastery Learning in classical shows an increase of 54% to 85%.The conclusions that can be drawn after research and analysis, namely: (1) Improve student activity and (2) Improving student learning outcomes. The suggestions are taken: (1) To the teachers of Physics in order to design a strategy to be more innovative concept maps, and trying to implement them in teaching Physics and (2) For the next researcher is able to review the other, such as motivation, characteristic ways of thinking and others.Keywords : Mind Mapping , activities, achievement